Quantum discord as resource for remote state preparation - Dakić, B; Lipp, Y; Ma, X; Ma, X; Ringbauer, M; Kropatschek, S; Barz, S; Paterek, T; Vedral, V; Vedral, V; Zeilinger, A; Zeilinger, A; et al. (2012)
The existence of better-than-classical quantum information processing (QIP) models which consume very little or no entanglement suggests that separable or weakly entangled states could be extremely useful tools for information processing as they are much easier to prepare and control even in dissipative environments. It has been proposed that a resource of advantage is the generation of quantum discord, a measure of non-classical correlations that includes entanglement as a subset. Here we show that quantum discord is the necessary resource for quantum remote state preparation. We explicitly show that the geometric measure of quantum discord is related to the fidelity of this task, which provides its operational meaning. Our results are experimentally demonstrated using photonic quantum systems. Moreover, we demonstrate that separable states with non-zero quantum discord can outperform entangled states. Therefore, the role of quantum discord might provide fundamental insights for resource-efficient QIP. © 2012 Macmillan Publishers Limited. All rights reserved.